Child Right- Based Approach Dalam Peningkatan Self- Esteem Anak Usia Sekolah Dasar - Said, Ratna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
This study aims to determine the Child-Right Based Approach in increasing Self-Esteem of elementary school aged children. This research is a qualitative research which is literature study or library research. Child Right-Based Approach in increasing self-esteem of elementary school age children: a) non-discrimination; the shortcomings of the child do not make the child lose his / her rights; b) the right to survival and development; c) the child's right to participate in decision making can increase children's self-esteem; 4) child-friendly laws